Fluorinated poly (aryl-piperidine) anion exchange membrane containing flexible biphenyl and preparation method thereof

CN119275318APending Publication Date: 2025-01-07CHANGCHUN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411579038.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

但是,目前阴离子交换膜面临着离子传导率低,耐碱稳定性差,尺寸稳定性差等等问题

Benefits of technology

本发明首先提供了含柔性联苯的氟化聚(芳基-哌啶)的阴离子交换膜。其中,所述的哌啶阳离子和氟化基团的摩尔比为9:1,柔性联苯和三联苯的摩尔比为1:(3,4,9,17)或者(0:1)。在主链上引入柔性联苯,有利于促进阳离子聚集,同时与疏水的氟化基团构建更加明显的微相分离结构,有效的提高膜的离子传导性。此外,高刚性的芳环和疏水的氟化基团的引入,有效提高的膜的力学性能和尺寸稳定性。无醚骨架和具有大空间位阻的哌啶阳离子的引入,有效的缓解OH-进攻,提高膜的耐碱性。实验结果表明,本发明的含柔性联苯的氟化聚(芳基-哌啶)的主链型阴离子交换膜在80oC时的离子传导率为90.37 mS cm-1-151.02 mS cm-1,阴离子交换膜的厚度为23-26 μm。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275318A_ABST
    Figure CN119275318A_ABST
Patent Text Reader

Abstract

The invention discloses a fluorinated poly (aryl-piperidine) anion exchange membrane containing flexible biphenyl. Wherein the molar ratio of the piperidine cation to the fluorinated group is 9: 1, and the molar ratio of the flexible biphenyl to the terphenyl is 1: (3, 4, 9, 17) or (0: 1). Due to the introduction of flexible biphenyl containing a foldable rotary flexible alkyl chain, the aggregation of piperidine cation groups is promoted, and a more obvious hydrophilic / hydrophobic microphase separation structure is constructed with fluorinated groups, so that the conductivity is effectively improved. Meanwhile, no ether bond skeleton and introduction of piperidine cation groups with large steric hindrance can relieve OH <-> ion attack and improve the alkali-resistant stability. Due to hydrophobic fluorinated groups and high-rigidity aryl rings, excellent mechanical properties and dimensional stability are kept. Experimental results show that the anion conductivity of the anion exchange membrane at the temperature of 80 DEG C is 90.37 mS cm <-1 >-151.02 mS cm <-1 >, and the thickness of the anion exchange membrane is 23-26 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the two fields of anion exchange membrane fuel cells and polymer chemistry, and specifically relates to a fluorinated poly (aryl-piperidine) anion exchange membrane containing flexible biphenyl and a preparation method thereof. Background Art

[0002] With the development of society, the excessive consumption of fossil fuels and environmental pollution are becoming more and more serious, so the development of new energy is urgent. Among them, hydrogen energy stands out for its clean and environmentally friendly characteristics. At the same time, anion exchange membrane fuel cell is a hydrogen energy conversion device that efficiently utilizes energy. Due to its advantages such as fast redox reaction, use of non-precious metal catalysts to reduce costs and low fuel permeability, it is expected to replace the currently commercialized proton exchange membrane fuel cell. As one of the core components of anion exchange membrane fuel cells, anion exchange membrane has always received extensive attention and research. However, at present, anion exchange membranes face problems such as low ion conductivity, poor alkali stability, and poor dimensional stability. Therefore, the preparation of flexible biphenyl-containing fluorinated poly (aryl-piperidine) polymers with excellent ionic conductivity, mechanical properties and alkali stability has become the most potential anion exchange membrane material, and the synthesis method is simple and has attracted much attention.

[0003] In the preparation process of fluorinated poly(aryl-piperidine) anion exchange membrane containing flexible biphenyl, the introduction of flexible biphenyl containing foldable and rotatable flexible alkyl chains promoted the aggregation of piperidine cationic groups and constructed a more obvious hydrophilic / hydrophobic microphase separation structure with the fluorinated groups, effectively improving the conductivity. At the same time, the introduction of piperidine cationic groups without ether bond skeleton and with large steric hindrance can alleviate the OH - Ion attack improves its alkali resistance stability. The hydrophobic fluorinated groups and high rigidity aromatic rings enable it to maintain excellent mechanical properties and dimensional stability. Summary of the invention

[0004] In order to overcome the defects existing in the prior art, the present invention mainly provides a method for preparing a fluorinated poly (aryl-piperidine) anion exchange membrane containing flexible biphenyl. The present invention promotes the aggregation of piperidine cationic groups by introducing flexible biphenyl containing flexible alkyl chains into the fluorinated poly (aryl-piperidine) copolymer, and constructs a more obvious hydrophilic / hydrophobic microphase separation structure with the fluorinated group, thereby effectively improving the conductive performance. At the same time, the hydrophobic fluorinated group and the high rigidity aromatic ring enable it to maintain excellent mechanical properties while inhibiting swelling. The use of the piperidine cationic group with no ether bond skeleton and large steric hindrance can alleviate the OH - Ion attack, improving its alkali resistance stability.

[0005] The present invention is achieved through the following technical solutions: The present invention provides a preparation process of a fluorinated poly(aryl-piperidine) anion exchange membrane containing flexible biphenyl, wherein the molar ratio of piperidinium cations to fluorinated groups is 9:1, and the molar ratio of flexible biphenyl to terphenyl is 1:(3, 4, 9, 17) or (0:1).

[0006] In the above scheme, the thickness of the flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane is 23-26 μm.

[0007] The present invention also provides a method for preparing a fluorinated poly (aryl-piperidine) anion exchange membrane containing flexible biphenyl, comprising the following steps: Step 1: preparing a fluorinated poly(aryl-piperidine) polymer containing a flexible biphenyl; Step 2: quaternizing the fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl obtained in step 1 to obtain a quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl; Step 3: The quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl obtained in step 2 is dissolved in dimethyl sulfoxide solvent, dried and coated to obtain a series of fluorinated poly(aryl-piperidine) anion exchange membranes containing flexible biphenyl.

[0008] Preferably, the monomer is terphenyl, 1,2-diphenylethane, N-methyl-4-piperidone, hexafluoroacetone, or methyl iodide.

[0009] Preferably, the solvent is one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP) or dimethyl sulfoxide (DMSO).

[0010] Preferably, the catalyst is trifluoroacetic acid (TFA) and trifluoromethanesulfonic acid (TFSA).

[0011] In the above scheme, the preparation method of the fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl in step 1 is: Place p-terphenyl, 1,2-diphenylethane, N-methyl-4-piperidone, hexafluoroacetone and dichloromethane in a three-necked flask under an ice bath. Stir for 30 min, slowly add trifluoroacetic acid, and after the smoke dissipates, slowly add trifluoromethanesulfonic acid. Then, at 0 o After continuous stirring at 400 °C for 5 h, the dark blue super-viscous product was poured into a potassium carbonate solution to precipitate a light yellow solid, which was soaked for a period of time, sheared, washed with deionized water for multiple times, boiled to neutrality, dried, and collected for later use to obtain a fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl.

[0012] In the above scheme, the preparation method of the quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl in step 2 is: The fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl obtained in step 1 is dissolved in N-methylpyrrolidone (NMP), potassium carbonate and iodomethane are added, and the reaction is carried out under light-proof conditions. The light yellow solution is filtered into ethyl acetate to precipitate a light yellow solid, which is washed alternately with ethyl acetate and deionized water, and dried to obtain a quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl.

[0013] In the above scheme, the specific operation of step three is: Dissolve the quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl obtained in step 2 in dimethyl sulfoxide (DMSO) to form a uniform mixed solution. Use a syringe and filter to drop it onto a clean 8 cm × 8 cm glass plate and place it in a 60-80 o C oven for 48-72 hours, remove the membrane with deionized water, and then soak the membrane in NaOH solution for 24-36 hours to obtain OH containing flexible biphenyl fluorinated poly (aryl-piperidine) for fuel cell - Type anion exchange membrane.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention first provides an anion exchange membrane of fluorinated poly (aryl-piperidine) containing flexible biphenyl. Among them, the molar ratio of the piperidine cation and the fluorinated group is 9:1, and the molar ratio of the flexible biphenyl and the terphenyl is 1: (3, 4, 9, 17) or (0:1). The introduction of flexible biphenyl on the main chain is conducive to promoting cation aggregation, and at the same time constructs a more obvious microphase separation structure with the hydrophobic fluorinated group, effectively improving the ion conductivity of the membrane. In addition, the introduction of highly rigid aromatic rings and hydrophobic fluorinated groups effectively improves the mechanical properties and dimensional stability of the membrane. The introduction of piperidine cations without ether skeletons and with large steric hindrance effectively alleviates OH - The experimental results show that the main chain type anion exchange membrane containing flexible biphenyl fluorinated poly (aryl-piperidine) of the present invention has good alkali resistance at 80 o The ionic conductivity at C is 90.37 mS cm -1 -151.02 mS cm -1 , the thickness of the anion exchange membrane is 23-26 μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a curve showing the change in ion conductivity of the main chain anion exchange membrane of the fluorinated poly(aryl-piperidine) containing flexible biphenyl prepared in Examples 1, 2, 3, 4 and 5 of the present invention; Figure 2 This is a curve showing the thermal stability change of the main chain anion exchange membrane of the fluorinated poly(aryl-piperidine) containing flexible biphenyl prepared in Examples 1, 2, 3, 4 and 5 of the present invention. Specific implementation methods The present invention will be further described below in conjunction with the embodiments.

[0016] Example 1 A method for preparing a fluorinated poly (aryl-piperidine) anion exchange membrane containing flexible biphenyl for a fuel cell, the specific steps are as follows: (1) Under nitrogen protection, place p-terphenyl (2.3 g, 0.01 mol), N-methyl-4-piperidone (1.143 g, 0.0099 mol), hexafluoroacetone (0.247 g, 0.0011 mol) and dichloromethane (12 ml) in a three-necked flask under an ice bath. Stir for 30 min, slowly add 1.35 ml of trifluoroacetic acid (TFA), and after the smoke dissipates, slowly add 8.5 ml of trifluoromethanesulfonic acid (TFSA). Then, at 0 o After continuous stirring at 40 °C for 5 h, the dark blue super-viscous product was poured into a 1 M K2CO3 (300 ml) solution to precipitate a light yellow solid, which was soaked for a period of time, sheared, washed with deionized water several times, boiled to neutrality, dried, and collected for later use.

[0017] (2) The polymer obtained in step (1) was weighed (0.3 g, 0.000816 mol) and dissolved in NMP (12 ml). K2CO3 (0.228 g, 0.00163 mol) and iodomethane (306 μl, 0.0049 mol) were added and incubated at 40 °C in a dark environment. o C for 48 h, the light yellow solution was filtered into ethyl acetate to precipitate a light yellow solid, which was washed alternately with EA and deionized water, dried and collected for later use.

[0018] (3) Weigh 0.3 g of the polymer obtained in step (2) and dissolve it in 10 ml of dimethyl sulfoxide. Stir magnetically at room temperature for 24 h to obtain a uniform mixed solution. Use a syringe and filter to drop the obtained casting solution onto a clean 8 cm × 8 cm clean glass plate and place it in 80 o C oven for 48 hours, and then naturally cooled to room temperature and removed from the membrane in deionized water. The membrane was immersed in 1 mol / L sodium hydroxide solution for 24 hours to obtain a fluorinated poly (aryl-piperidinyl) OH containing flexible biphenyl. - The obtained flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane was heated at 80 oC, the conductivity of the membrane was 90.37 mS cm -1 , the film thickness is 23 μm, at 30 o C, its conductivity is 37.93 mS cm -1 .

[0019] Example 2 (1) Under nitrogen protection, place p-terphenyl (2.3 g, 0.01 mol), 1,2-diphenylethane (0.205 g, 0.0011 mol), N-methyl-4-piperidone (1.27 g, 0.011 mol), hexafluoroacetone (0.275 g, 0.0012 mol) and dichloromethane (12 ml) in a three-necked flask under an ice bath. Stir for 30 min, slowly add 1.35 ml of trifluoroacetic acid (TFA), and after the smoke dissipates, slowly add 9.5 ml of trifluoromethanesulfonic acid (TFSA). Then, at 0 o After continuous stirring at 40 °C for 5 h, the dark blue super-viscous product was poured into a 1 M K2CO3 (300 ml) solution to precipitate a light yellow solid, which was soaked for a period of time, sheared, washed with deionized water several times, boiled to neutrality, dried, and collected for later use.

[0020] (2) The polymer obtained in step (1) was weighed (0.3 g, 0.00092 mol) and dissolved in NMP (12 ml). K2CO3 (0.256 g, 0.00184 mol) and iodomethane (345 μl, 0.00552 mol) were added and incubated at 40 °C in a dark environment. o C for 48 h, the light yellow solution was filtered into ethyl acetate to precipitate a light yellow solid, which was washed alternately with EA and deionized water, dried and collected for later use.

[0021] (3) Weigh 0.3 g of the polymer obtained in step (2) and dissolve it in 10 ml of dimethyl sulfoxide. Stir magnetically at room temperature for 24 h to obtain a uniform mixed solution. Use a syringe and filter to drop the obtained casting solution onto a clean 8 cm × 8 cm clean glass plate and place it in 80 o C oven for 48 hours, and then naturally cooled to room temperature and removed from the membrane in deionized water. The membrane was immersed in 1 mol / L sodium hydroxide solution for 24 hours to obtain a fluorinated poly (aryl-piperidinyl) OH containing flexible biphenyl. - The obtained flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane was heated at 80 o C, the conductivity of the membrane was 109.67 mS cm -1 , the film thickness is 24 μm, at 30 oC, its conductivity is 42.57 mS cm -1 .

[0022] Example 3 (1) Under nitrogen protection, place p-terphenyl (2.3 g, 0.01 mol), 1,2-diphenylethane (0.324 g, 0.00176 mol), N-methyl-4-piperidone (1.35 g, 0.01165 mol), hexafluoroacetone (0.292 g, 0.0013 mol) and dichloromethane (12 ml) in a three-necked flask under an ice bath. Stir for 30 min, slowly add 1.35 ml of trifluoroacetic acid (TFA), and after the smoke dissipates, slowly add 10 ml of trifluoromethanesulfonic acid (TFSA). Then, at 0 o After continuous stirring at 40 °C for 5 h, the dark blue super-viscous product was poured into a 1 M K2CO3 (300 ml) solution to precipitate a light yellow solid, which was soaked for a period of time, sheared, washed with deionized water several times, boiled to neutrality, dried, and collected for later use.

[0023] (2) The polymer obtained in step (1) was weighed (0.3 g, 0.0008338 mol) and dissolved in NMP (12 ml). K2CO3 (0.2328 g, 0.00167 mol) and iodomethane (313 μl, 0.005 mol) were added and incubated at 40 °C in a dark environment. o C for 48 h, the light yellow solution was filtered into ethyl acetate to precipitate a light yellow solid, which was washed alternately with EA and deionized water, dried and collected for later use.

[0024] (3) Weigh 0.3 g of the polymer obtained in step (2) and dissolve it in 10 ml of dimethyl sulfoxide. Stir magnetically at room temperature for 24 h to obtain a uniform mixed solution. Use a syringe and filter to drop the obtained casting solution onto a clean 8 cm × 8 cm clean glass plate and place it in 80 o C oven for 48 hours, and then naturally cooled to room temperature and removed from the membrane in deionized water. The membrane was immersed in 1 mol / L sodium hydroxide solution for 24 hours to obtain a fluorinated poly (aryl-piperidinyl) OH containing flexible biphenyl. - The obtained flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane was heated at 80 o C, the conductivity of the membrane was 118.99 mS cm -1 , the film thickness is 26 μm, at 30 o C, its conductivity is 51.03 mS cm -1 .

[0025] Example 4 (1) Under nitrogen protection, place p-terphenyl (2.3 g, 0.01 mol), 1,2-diphenylethane (0.46 g, 0.0025 mol), N-methyl-4-piperidone (1.429 g, 0.012375 mol), hexafluoroacetone (0.309 g, 0.001375 mol) and dichloromethane (12 ml) in a three-necked flask under an ice bath. Stir for 30 min, slowly add 1.35 ml of trifluoroacetic acid (TFA), and after the smoke dissipates, slowly add 10 ml of trifluoromethanesulfonic acid (TFSA). Then, at 0 o After continuous stirring at 40 °C for 5 h, the dark blue super-viscous product was poured into a 1 M K2CO3 (300 ml) solution to precipitate a light yellow solid, which was soaked for a period of time, sheared, washed with deionized water several times, boiled to neutrality, dried, and collected for later use.

[0026] (2) The polymer obtained in step (1) was weighed (0.3 g, 0.00084 mol) and dissolved in NMP (12 ml). K2CO3 (0.2347 g, 0.00168 mol) and iodomethane (315 μl, 0.00504 mol) were added and incubated at 40 °C in a dark environment. o C for 48 h, the light yellow solution was filtered into ethyl acetate to precipitate a light yellow solid, which was washed alternately with EA and deionized water, dried and collected for later use.

[0027] (3) Weigh 0.3 g of the polymer obtained in step (2) and dissolve it in 10 ml of dimethyl sulfoxide. Stir magnetically at room temperature for 24 h to obtain a uniform mixed solution. Use a syringe and filter to drop the obtained casting solution onto a clean 8 cm × 8 cm clean glass plate and place it in 80 o C oven for 48 hours, and then naturally cooled to room temperature and removed from the membrane in deionized water. The membrane was immersed in 1 mol / L sodium hydroxide solution for 24 hours to obtain a fluorinated poly (aryl-piperidinyl) OH containing flexible biphenyl. - The obtained flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane was heated at 80 o C, the conductivity of the membrane was 131.42 mS cm -1 , the film thickness is 25 μm, at 30 o C, its conductivity is 59.63 mS cm -1 .

[0028] Example 5 (1) Under nitrogen protection, place terphenyl (2.3 g, 0.01 mol), 1,2-diphenylethane (0.614 g, 0.00334 mol), N-methyl-4-piperidone (1.524 g, 0.0132 mol), hexafluoroacetone (0.33 g, 0.00147 mol) and dichloromethane (12 ml) in a three-necked flask under an ice bath. Stir for 30 min, slowly add 1.35 ml of trifluoroacetic acid (TFA), and after the smoke dissipates, slowly add 10 ml of trifluoromethanesulfonic acid (TFSA). Then, after continuous stirring at 0°C for 5 h, pour the dark blue super-viscous product into 1 M K2CO3 (300 ml) solution to precipitate a light yellow solid, soak for a period of time, shear, wash with deionized water several times, boil until neutral, dry, and collect for later use.

[0029] (2) The polymer obtained in step (1) was weighed (0.3 g, 0.00094 mol) and dissolved in NMP (12 ml). K2CO3 (0.263 g, 0.00188 mol) and iodomethane (352 μl, 0.00564 mol) were added and incubated at 40 °C in a dark environment. o C for 48 h, the light yellow solution was filtered into ethyl acetate to precipitate a light yellow solid, which was washed alternately with EA and deionized water, dried and collected for later use.

[0030] (3) Weigh 0.3 g of the polymer obtained in step (2) and dissolve it in 10 ml of dimethyl sulfoxide. Stir magnetically at room temperature for 24 h to obtain a uniform mixed solution. Use a syringe and filter to drop the obtained casting solution onto a clean 8 cm × 8 cm clean glass plate and place it in 80 o C oven for 48 hours, and then naturally cooled to room temperature and removed from the membrane in deionized water. The membrane was immersed in a 1 mol / L sodium hydroxide solution for 24 hours to obtain a quaternized fluorinated poly (aryl-piperidinyl) OH containing flexible biphenyl. - The obtained flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane was heated at 80 o C, the conductivity of the membrane was 151.02 mS cm -1 , the film thickness is 23 μm, at 30 o C, its conductivity is 64.67 mScm -1 .

[0031] Figure 1 The graph is a graph showing the ion conductivity of the anion exchange membranes prepared in Example 1, Example 2, Example 3, Example 4 and Example 5 of the present invention as a function of temperature. Among them, the ion conductivity of the anion exchange membrane prepared in Example 5 is the highest.

[0032] Figure 2 The following is a graph showing the thermal weight loss curves of the anion exchange membranes prepared in Examples 1, 2, 3, 4 and 5 of the present invention. The poly(aryl-piperidine) anion exchange membrane containing flexible biphenyl has excellent thermal stability. There are three decomposition stages in the TGA curve. The first decomposition stage is at 40 o C-110 o C. The weight loss in this stage is due to the evaporation of residual water and residual solvent in the film. The second decomposition stage is at 300 o C-400 o C, the weight loss in this stage is due to the degradation of piperidinium cation. o The degradation of the polymer backbone occurred after C. The results showed that the AEMs had good thermal stability and could meet the practical application of commercial fuel cells.

[0033] The description of the above embodiments is only used to help understand the method of the present invention and its core concept. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. Fluorinated poly (aryl-piperidine) anion exchange membrane containing flexible biphenyl. First, a fluorinated poly (aryl-piperidine) polymer containing flexible biphenyl was prepared by condensation polymerization under the catalysis of superacid. Then, iodomethane was used to quaternize the piperidine site to completely quaternize it into N + ions to obtain a quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl. The molar ratio of piperidinium cation and fluorinated group is 9:1, and the molar ratio of flexible biphenyl and terphenyl is 1:(3, 4, 9, 17) or (0:1). Then, the film is laid by a casting method to obtain a fluorinated poly (aryl-piperidine) anion exchange membrane containing flexible biphenyl.

2. The fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl according to claim 1, wherein the preparation method is as follows: under nitrogen protection, a mol of p-terphenyl, b mol of 1,2-diphenylethane, c mol of N-methyl-4-piperidone and d mol of hexafluoroacetone and dichloromethane (12 ml) are placed in a three-necked flask under an ice bath. Stir for 30 min, slowly add 1.35 ml of trifluoroacetic acid (TFA), and after the smoke dissipates, slowly add 9.5 ml of trifluoromethanesulfonic acid (TFSA). Then, at 0 o After continuous stirring at 40 °C for 5 h, the dark blue super-viscous product was poured into a 1 M K2CO3 (300 ml) solution to precipitate a light yellow solid, which was soaked for a period of time, sheared, washed with deionized water for several times, boiled to neutrality, dried, and collected for later use to obtain a fluorinated poly (aryl-piperidine) polymer containing flexible biphenyl, wherein: a+b=1.1(c+d).

3. The fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl according to claim 2, wherein the monomers are terphenyl, 1,2-diphenylethane, N-methyl-4-piperidone, and hexafluoroacetone. The catalyst is trifluoroacetic acid and trifluoromethanesulfonic acid, and the solvent is dichloromethane.

4. The quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl according to claim 1, wherein the preparation method is as follows: weigh a mol of the fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl and dissolve it in NMP (12 ml), add b mol of K2CO3 and c mol of methyl iodide after it is fully dissolved, react at 40°C for 24-48 h under light-proof conditions, filter the light yellow solution into ethyl acetate, precipitate a light yellow solid precipitate, wash it alternately with EA and deionized water, dry it, and collect it for later use to obtain the quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl.

5. In the quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl according to claim 4, the molar ratio of potassium carbonate to methyl iodide in the fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl is 1:1.2-1.5:4-8.

6. The method for preparing a flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane according to claim 1, comprising the following steps: Step 1: preparing a fluorinated poly(aryl-piperidine) polymer containing a flexible biphenyl; Step 2: quaternizing the fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl obtained in step 1 to obtain a quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl; Step 3: The quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl obtained in step 2 is dissolved in dimethyl sulfoxide solvent, dried and coated to obtain a series of fluorinated poly(aryl-piperidine) anion exchange membranes containing flexible biphenyl.

7. The method for preparing a flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane according to claim 6, characterized in that: The preparation method of the fluorinated poly (aryl-piperidine) polymer containing flexible biphenyl in the above step 1 is as follows: under nitrogen protection, p-terphenyl, 1,2-diphenylethane, 1-methyl-4-piperidone, hexafluoroacetone and dichloromethane are placed in a three-necked flask under an ice bath. Stir for 30 minutes, slowly add trifluoroacetic acid (TFA), and after the smoke dissipates, slowly add trifluoromethanesulfonic acid (TFSA). Then, at 0 o After continuous stirring at 400 °C for 5 h, the dark blue super-viscous product was poured into a 1 M K2CO3 solution to precipitate a light yellow solid, which was soaked for a period of time, sheared, washed with deionized water for several times, boiled to neutrality, dried, and collected for later use.

8. The method for preparing a fluorinated poly(aryl-piperidine) anion exchange membrane containing flexible biphenyl according to claim 6, characterized in that: The preparation method of the quaternized fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl in the above step 2 is as follows: weigh the fluorinated poly(aryl-piperidine) polymer containing flexible biphenyl and dissolve it in NMP. After it is fully dissolved, add K2CO3 and iodomethane, and heat it at 40 °C in a dark environment. o C for 24-48 hours, filter the light yellow solution into ethyl acetate to precipitate a light yellow solid, wash it alternately with EA and deionized water, dry it and collect it for later use.

9. The method for preparing a flexible biphenyl-containing fluorinated poly (aryl-piperidine) anion exchange membrane according to claim 6, characterized in that: The specific operation steps of the above step 3 membrane laying are to dissolve the quaternized flexible biphenyl-containing fluorinated poly (aryl-piperidine) polymer in DMSO to form a uniform mixed solution. Use a syringe and filter to drop it onto a clean 8 cm × 8 cm clean glass plate, and place it in a 60-80 o C oven for 48-72 hours, remove the membrane with deionized water, and then soak the membrane with NaOH solution for 24-36 hours to obtain OH containing flexible biphenyl fluorinated poly (aryl-piperidine) for fuel cell - Type anion exchange membrane.

Citation Information

Cited By

  • Fluorine-free poly (phenylene alkylene) pyridyl anion exchange membrane and preparation method thereof

    CN121975075A